Other proprietary brand assets and competitive advantage in beer products in Kabale District, South Western Uganda - Agaba, Moses; Sunday, Arthur (Special Journal of Politics and Economic Sustainability, 2020)
In the current business environment, firms are required to be more competitive and hostile. Other proprietary brand asset is used by business organizations to gain competitive advantage. This study adopted the resource-based business model that provides a framework for identifying unique set of resources and shifts the approach of assessing competitive advantage from the external to the internal environment that is the resource power This is a descriptive questionnaires-based survey of 1,783 wholesalers, retailers, customers, brand and marketing managers of Nile Special Lager, Eagle Lager, Senator Extra Lager, Club and Bell beer products sold in Kabale District of Uganda. Simple random sampling was used to select alcoholic beverages products and producers while purposive sampling was adopted to select shopping centers where consumer information was collected after pilot marketing investigation.
Keywords: Proprietary Brand Assets; Competitive Advantage; Beer; Kabale; Uganda